Integrated Language Skills through Theme-Based Learning and The Mediation of Flipped Classroom in Fourth Grade Students at La Colina School (2016)
The purpose of this study was to examine how combining theme-based learning with flipped classroom mediation can foster the use of the English language in an EFL group of primary learners, and maximize their interaction, participation and practice of English outside the regular classroom setting. The research was conducted at La Colina School in Bogotá, a mixedgender bilingual school located in Casa Blanca, Suba. Twenty 9- to10-year-old kids from 4th grade participated in the research. They have an A2 level of English, based on the Common European Framework of reference for languages. The study was done in a period of eight months in which students were asked to work on various activities on an online classroom, which included instructive videos prior to the face to face lesson, games, writing, reading, listening and speaking activities. The findings of the study showed that using a theme-based instruction and the mediation of flipped classroom enabled and encouraged integrated language skills effectively. Using theme-based instruction made the content meaningful and relevant and effectively integrated the four language skills in a real-life context. The flipped classroom provided the means for students to learn and practice outside of class and students had the opportunity to practice any time they wanted and use the tools and information to get ready for their face to face encounter, which had an impact on their language achievement and the use of English. Students responded well to the use of the flipped classroom and perceived the experience as a positive one. They took more control over their learning process and became more independent. This mediation also saved classroom time since the time that used to be spent introducing new concepts was used to practice.